2013
DOI: 10.4103/2278-330x.119921
|View full text |Cite
|
Sign up to set email alerts
|

Oncological safety of immediate rectus abdominis myocutaneous breast reconstruction in patients with locally advanced disease (stage IIb and III)

Abstract: Background:The management of locally advanced (Stage IIb and III) breast cancer is challenging. It often includes multimodal treatment with systemic therapy and/or radiation therapy and surgery. Immediate breast reconstruction has not traditionally been performed in these patients. We review the results of immediate rectus abdominis musculo-cutaneous (TRAM/VRAM) flap in 60 patients treated for Stage IIb and III breast cancer.Materials and Methods:Data were collected prospectively on 60 patients diagnosed with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…Howes et al [ 22 ] showed that IBR after mastectomy significantly improved the postoperative cosmetic results without affecting the long-term efficacy, which could obtain better satisfaction and body image and ensure the postoperative quality of life. And IBR is able to reduce the occurrence of postoperative complications [ 23 ], while it does not increase local tumor recurrence and distant metastasis [ 24 , 25 ]. In this study, it was found that IBR significantly improved the breast aesthetic effect, postoperative skin texture, appearance of the reconstructed breast, and nipple shape, with high safety.…”
Section: Discussionmentioning
confidence: 99%
“…Howes et al [ 22 ] showed that IBR after mastectomy significantly improved the postoperative cosmetic results without affecting the long-term efficacy, which could obtain better satisfaction and body image and ensure the postoperative quality of life. And IBR is able to reduce the occurrence of postoperative complications [ 23 ], while it does not increase local tumor recurrence and distant metastasis [ 24 , 25 ]. In this study, it was found that IBR significantly improved the breast aesthetic effect, postoperative skin texture, appearance of the reconstructed breast, and nipple shape, with high safety.…”
Section: Discussionmentioning
confidence: 99%
“…VRAM, in turn, is a versatile flap, associated with a low rate of complications, but it generates fragility in the abdominal wall, as well as the presence of a vertical scar 7,11 , with less necrosis compared to TRAM 12 .…”
Section: Discussionmentioning
confidence: 99%
“…In the case of reconstruction of defects after mastectomy in locally advanced tumors, with the need to use myocutaneous flaps, the latissimus dorsi flap is the option 5 . However, there is space for the use of the abdominal external oblique muscle flap 6 , TRAM or VRAM 7 . A case in which VRAM was used was presented here, along with a discussion on the factors related to its choice and results.…”
Section: Introductionmentioning
confidence: 99%
“…58 These flaps are used when postmastectomy defect area is more extensive and can usually be performed by breast specialists, oncological surgeons, and plastic Note: Adapted from Vieira et al 32 New publications included. 33,43,46,[48][49][50]53 Abbreviations: EOMF, external oblique myocutaneous flap; ITADE, ipsilateral thoracoabdominal dermofat flap; LD, latissimus dorsi; MEOMF, modified EOMF. surgeons; generally, they are associated with a lower rate of flap necrosis.…”
Section: Myocutaneous Flapsmentioning
confidence: 99%
“…Figure 2C, right panel) has the advantages of fast execution and acceptable complication rates, and it does not require a change in the patient's position during surgery; however, it is associated with partial necrosis. 50 One publication described a technical modification that allowed the resection of more extensive areas and was associated with high rates of necrosis, 33 defects, 54,55 with few series describing its use for reconstruction after LABC surgery 53 or closure of the chest wall. 51 In studies evaluating case series exclusively using this flap for primary closure of patients with tumors, 51,54,55 the VRAM rate of necrosis was 11.5%, although it was lower when used exclusively for patients with breast cancer(3.6%).…”
Section: Myocutaneous Flapsmentioning
confidence: 99%